A randomized, three-period crossover study of umeclidinium as monotherapy in adult patients with asthma. Issue 1 (January 2015) - Lee, Laurie A.; Briggs, Anne; Edwards, Lisa D.; Yang, Shuying; Pascoe, Steven
Summary Background To our knowledge, no studies in patients with asthma have assessed a long-acting muscarinic antagonist in the absence of inhaled corticosteroids (ICS). Objective Evaluate the dose–response, efficacy, and safety of umeclidinium (UMEC) in patients with asthma not receiving ICS. Methods In this double-blind, three-period crossover study, 350 subjects were randomized to a sequence of three of eight inhaled treatments: UMEC 15.6, 31.25, 62.5, 125, or 250 mcg once daily (OD), UMEC 15.6 or 31.25 mcg twice daily (BID), or placebo, administered for 14 days (12–14-day washout). Trough forced expiratory volume in one second (FEV1), 0–24-h weighted mean (WM) FEV1, and safety were assessed. Serial spirometry and pharmacokinetic assessments were performed in a subgroup. Results Subjects had a mean baseline pre- and post-bronchodilator FEV1 of 71% and 88% predicted, respectively. Significant improvements in change from baseline trough FEV1 were observed for UMEC 15.6 OD (0.066 L; p = 0.036) and UMEC 125 OD (0.088 L; p = 0.005) versus placebo, but not other OD or BID doses. UMEC increased 0–24-h WM FEV1 versus placebo (0.068–0.121 L [p ≤ 0.017] with no clear dose–response). Treatment differences were similar for corresponding OD and BID doses in serial assessments. UMEC was rapidly absorbed, with evidence of some accumulation. The incidence of on-treatment adverse events was 9–21% for UMEC and 12% for placebo. There were no treatment-related effects on laboratory parameters. Conclusion The modest trough FEV1 improvements did not conclusively support a therapeutic benefit of UMEC in non-ICS treated patients with asthma. ClinicalTrials.gov NCT01641692.